Inside Cover: Assembly of Multi‐Phthalocyanines on a Porphyrin Template by Fourfold Rotaxane Formation (Chem. Eur. J. 35/2016). Issue 35 (12th August 2016) - Yamada, Yasuyuki; Kato, Tatsuhisa; Tanaka, Kentaro
Abstract : Self‐organization of phthalocyanines has been programmed on a porphyrin template. Two phthalocyanines with four peripheral crown ether units are stacked cofacially on a porphyrin bearing four alkylammonium chains, in accordance with the number of ammonium groups on the side chain, through fourfold rotaxane formation. Significant electronic interaction is observed between the closely stacked phthalocyanines. More information can be found in the Full Paper by K. Tanaka, et al. onpage 12371 ff.